Attitude, stigma and working alliance in the counseling relationship among university students: A conceptual paper - Siti Nurafif Naim; Chua, Bee Seok; Muhammad Idris Bullare @ Bahari; Patricia Joseph Kimong (Fakulti Psikologi dan Pendidikan, 2021)
University students utilizing campus counseling services is still very low, despite easy accessibility and no fee if not minimal. Even when students may benefit from one, avoiding counseling may lead to unattended psychological problems that affect their academic achievement. Therefore, once a student enters counseling, the counselor has an important role in ensuring a strong working alliance in the relationship. Different psychotherapeutic approaches have long recognized the crucial component of working alliance in counseling, central to clients' change. Rupture in the working alliance may lead to reduced motivation returning to counseling. While attitude and stigma have been associated with counseling avoidance among university students in the Malaysian context, investigations into the three working alliance constructs based on Bordin's (1979) concept on the working alliance has not been adequately examined. The three components to the working alliance concept are as follows: (i) Goal; (ii) Task; and; (iii) Bond. The present conceptual paper discussed the role of disclosing psychological distress and intention to seek counseling in the relationship between attitude and stigma and working alliance among Malaysian university students. A conceptual framework is developed based on the reviewed literature guided by the theory of reasoned action and the theory of working alliance.